Developing Supply Chain Strategies for Enhancing the Productivity in Financial Sector: Evidence from Nigeria - I. Stella, Ezeh; K. Agbaeze, Emmanuel; Sr N. Ike, Mba; A. Abiodun, Olayinka (ExcelingTech, 2020)
This paper presents the impact of applying the supply chain strategies on the financial sector to optimize productivity and decreasing cost which will have a direct impact on the net income of the organization. The global economic situation in the last decade has left stakeholders in Nigerian financial sector struggling to meet up with profits/returns expected from them by their investors. The Nigerian financial sector has put in place a lot of mechanism to achieve their goals and one of such is reduction of employees running cost without taking into consideration the outcome of such decision at the long run. So this study proposes the effects of supply chain on the overall staff productivity in the financial sector, precisely the deposit money banks in Nigeria. The study set to test two hypotheses by means of SPSS and Spearman’s Rank Order Correlation coefficient for processing and analyzing of data collected using responses from 244 questionnaires distributed across the selected financial institutions in Port Harcourt, Rivers State, Nigeria and within acceptable Cronbach Alpha value of 0.7, results were interpreted and presented. The result of the analysis showed that there is a strong significant relationship between supply chain and staff productivity. The study found that there exist a great gap between the remunerations of casual and permanent employees thus leading to job dissatisfaction and lower productivity. The study recommends that government and management should develop supports toward employees input that will promote personal well-being and proletariat productivity while protecting them from exploitation by their employers in the financial institutions.